Strides for aberrations: The Electricity (Amendment) Bill, 2021 of India. (June 2022) - Shameem P, Mohammed; Chittedi, Krishna Reddy
Abstract: The article evaluates the provisions of the newly introduced Electricity (Amendment) Bill, 2021 by the government of India. As a holistic reform package for the electricity sector is coming after a long time, the bill deserves scrutiny regards its merits and other issues raised by various stakeholders. This article is an attempt to assess the bill with a focus on its implications for India's electricity sector. It examines the major features in the bill including the Renewable Purchase Obligation (RPO), the establishment of ECEA, enhanced payment security mechanism, the distribution Sublicense model, and the reforms in electricity pricing and subsidy system in the country. The repercussions of revamps in electricity pricing and subsidy system on farming communities and free electricity programs in many states incited opposition from stakeholders. It is found that the bill attempts to trespass the limits of the quasi-federal system in India, where it affects certain privileges of the state governments. The paper concludes that persisting crisis in the operations of the current regulatory paradigm in the electricity sector deserves a comprehensive renovation, but the abortive approach of the Bill on certain critical issues of the sector needs to be addressed. Highlights: An appraisal of the provisions of the newly introduced Electricity (Amendment) Bill, 2021 by the government of India is needed. The introduction of distribution sub licensee model is strongly opposed by state governments and workers unions. The existing constitutionally structured federal structure of India is challenged by the Bill. Consensus on entry of private distribution companies and subsidy system will decide the future of the bill.